2005
DOI: 10.1002/app.21372
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic approach on stabilization of LDPE in the presence of carnosic acid and related compounds. I. Thermal investigation

Abstract: ABSTRACT:Carnosic acid and similar compounds exhibit antioxidant behavior in a polyethylene matrix. Thermal resistance of LDPE was investigated at three temperatures (190, 200, and 210°C) by isothermal chemiluminescence. The main kinetic parameters: oxidation induction period (t i ), half oxidation time (t 1/2 ), maximum oxidation time (t max ), and propagation rate of oxidation (v ox max ) were calculated. The inhibition of thermal degradation is proved by the values of these parameters relative to unstabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…One way to minimize the effect of these extrusion conditions is using stabilizers like antioxidants. Different natural antioxidants, such as α‐tocopherol, carvacrol, carnosic acid, and synthetic, such as Irganox and BHT, have been used as polyolefin's stabilizers. Cerruti et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to minimize the effect of these extrusion conditions is using stabilizers like antioxidants. Different natural antioxidants, such as α‐tocopherol, carvacrol, carnosic acid, and synthetic, such as Irganox and BHT, have been used as polyolefin's stabilizers. Cerruti et al .…”
Section: Resultsmentioning
confidence: 99%
“…35 One way to minimize the effect of these extrusion conditions is using stabilizers like antioxidants. Different natural antioxidants, such as a-tocopherol, 3 carvacrol, 4 carnosic acid, 6 and synthetic, such as Irganox and BHT, 36 have been used as polyolefin's stabilizers. Cerruti et al 7 found that tomato extract, which contained more than 80 wt% lycopene, was a good thermal and processing stabilizer for polypropylene films when oxygen partial pressure was relatively low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulations of the European Union no. 10/2011 defines the use of additives in food packaging, because during the processing or storage of these materials, additives can migrate from the containers and packaging to the food, and for this reason many studies on the use of natural antioxidants to prevent the contact of food with synthetic antioxidants have been carried out in recent years; it is important to remark the excellent results obtained with α‐tocopherol at low concentrations (0.1–2%) for the stabilization of polyolefins1–4; carnosic acid has also been used (0.125, 0.25, 0.50, and 0.75%) to delay the thermal oxidation of PP5; on the other hand, the use of small additions (1 wt %) of essential oils of oregano, savory, and cinnamon to alginate–polycaprolactone copolymer has given interesting stabilizing properties6 as well as the use of essential oils of basil and thyme to provide higher stability to chitosan films has been reported 7. Flavonoids represent a generic group of natural compounds with attracting potential in polymer stabilization owing to the presence of phenolic compounds in their structure.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the large volume of literature available on the assessment of the antioxidant activity of rosemary extracts in a variety of unsaturated food lipids and food model compounds [15][16][17] , to our knowledge, there is scant information in the open literature on the stabilising performance of the main rosemary-antioxidants in polyolefins [18][19][20], and the antioxidant role of the ester derivatives of rosmarinic acid in polyolefins under M A N U S C R I P T…”
Section: Ca (I) C-oh (Ii) Ra (Iii)mentioning
confidence: 99%